2005
DOI: 10.1055/s-2004-817914
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Biochemical and Psychological Markers of Strenuous Training-Induced Fatigue

Abstract: The purpose of the study was to investigate whether severe fatigue, possibly leading to overreaching, could be diagnosed at an early stage by a combination of parameters. Seven well-trained male subjects (age [mean +/- SD]: 25.3 +/- 4.7 yr; body mass: 76 +/- 6.6 kg; VO2max: 61.1 +/- 7 ml.kg(-1).min(-1)) increased their training load by doubling their training volume and increasing the intensity by 15 % over a period of two weeks. Before and after this intensified training period subjects underwent a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
153
8
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(196 citation statements)
references
References 46 publications
(71 reference statements)
19
153
8
16
Order By: Relevance
“…This suggests that increasing the intensity, duration of training and the results of the games are linked to mood changes. Other research (Rietjens et al, 2005;Filaire et al, 2003;Silva et al, 2008), who studied the effect of an intense training program on biological modification and mood among professional footballers during the competitive period. They found physiological changes with increasing scores of POMS which explains the sharp increase in training load was associated with mood disturbances, decreased performance and biochemical changes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that increasing the intensity, duration of training and the results of the games are linked to mood changes. Other research (Rietjens et al, 2005;Filaire et al, 2003;Silva et al, 2008), who studied the effect of an intense training program on biological modification and mood among professional footballers during the competitive period. They found physiological changes with increasing scores of POMS which explains the sharp increase in training load was associated with mood disturbances, decreased performance and biochemical changes.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters as well as the white blood cells (WBCs) and their subpopulations have also been identified as indicators of muscle fatigue and overtraining (35,45). It has been shown that rugby sevens match (41) or high-intensity maximal tasks such as intermittent running, sprinting, jumping, resistance exercises (33,45), or Wingate test (16) resulted in transient leukocytosis and increase in biochemical markers of muscular damage for up to 10 days after exercise (10).…”
Section: Introductionmentioning
confidence: 99%
“…Embora os atletas aparentemente estivessem bem treinados, devido aos bons estados de estresse e recuperação (RESTQ-Sport) e aos bons valores de VFC, o tempo de reação foi significativamente maior após T1, mostrando que essa variável é sensível às alterações nas cargas de treinamento, o que indica ser esta variável um marcador relevante para o monitoramento das cargas de treinamento esportivo, principalmente em períodos de treinamentos extenuantes, como sugerido em outros estudos 1,4,19,28 . Contudo, não houve redução dos tempos de reação após T2, o que demonstra que a variável não foi sensível à redução de cargas de treinamento.…”
Section: Discussionunclassified
“…Sendo assim, muitos estudos têm buscado avaliar as cargas de treinamento por meio de instrumentos psicométricos, tais como o Perfil dos Estados de Humor -POMS 1,7,19 , e o Questionário de Estresse e Recuperação para Atletas -RESTQ-Sport 5,7,8,20,21 , que embora se mostrem sensíveis e expressivos, ainda apresentam resultados pouco consistentes, quando analisados de maneira isolada, além de possuírem baixa reprodutibilidade nos treinamentos diários 1 , devido à possibilidade de efeito de aprendizagem e grande número de itens, o que poderia causar desmotivação ao responder o questionário, originando respostas não fidedignas. Portanto, ainda não se tem conhecimento de um marcador objetivo, preciso e confiável, de aplicação prática e simplificada para o monitoramento do impacto da carga de treinamento sobre aspectos psicofisiológicos de atletas competitivos.…”
Section: Introductionunclassified
See 1 more Smart Citation